ab+ac+b^2+c^2+2bc
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
Xét tử :
\(\frac{a^2}{a^2+2bc}+\frac{b^2}{b^2+2ac}+\frac{c^2}{c^2+2ab}=\frac{a^2}{a^2+bc+(-ab-ac)}+\frac{b^2}{b^2+ac+(-ab-bc)}+\frac{c^2}{c^2+ab+(-bc-ac)}\)
\(=\frac{a^2}{a(a-b)-c(a-b)}+\frac{b^2}{b(b-c)-a(b-c)}+\frac{c^2}{c(c-a)-b(c-a)}\)
\(=\frac{a^2}{(a-c)(a-b)}+\frac{b^2}{(b-a)(b-c)}+\frac{c^2}{(c-a)(c-b)}\)
\(=\frac{a^2(c-b)+b^2(a-c)+c^2(b-a)}{(a-b)(b-c)(c-a)}\)
\(=\frac{(ab^2+bc^2+ca^2)-(a^2b+b^2c+c^2a)}{(ab^2+bc^2+ca^2)-(a^2b+b^2c+c^2a)}=1\)
Xét mẫu (tương tự bên tử)
\(\frac{bc}{a^2+2bc}+\frac{ac}{b^2+2ac}+\frac{ab}{c^2+2ab}=\frac{bc}{(a-c)(a-b)}+\frac{ac}{(b-a)(b-c)}+\frac{ab}{(c-a)(c-b)}\)
\(=\frac{bc(c-b)+ac(a-c)+ab(b-a)}{(a-b)(b-c)(c-a)}=\frac{(ab^2+bc^2+ca^2)-(a^2b+b^2c+c^2a)}{(a-b)(b-c)(c-a)}\)
\(=\frac{(ab^2+bc^2+ca^2)-(a^2b+b^2c+c^2a)}{(ab^2+bc^2+ca^2)-(a^2b+b^2c+c^2a)}=1\)
Do đó:
\(A=\frac{1}{1}=1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\Leftrightarrow\frac{a^2}{4}+b^2+c^2-ab+ac-2bc\ge0\)
\(\Leftrightarrow\left(\frac{a}{2}-b+c\right)^2\ge0\) (luôn đúng)
Dấu "=" xảy ra khi \(b=\frac{a}{2}+c\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) ta có : \(AB^2+AC^2=2AH^2+BH^2+CH^2\)
\(=2AM^2-2HM^2+\left(BM-HM\right)^2+\left(CM+HM\right)^2\)
\(=2AM^2-2HM^2+BM^2-2BM.HM+HM^2+CM^2+2CM.HM+HM^2\)
\(=2AM^2+BC^2-2BM.CM=2AM^2+BC^2-\dfrac{2BC^2}{4}\)
\(=2AM^2+\dfrac{BC^2}{2}\left(đpcm\right)\)
b) ta có : \(AC^2-AB^2=AH^2+HC^2-BH^2-AH^2\)
\(=HC^2-BH^2=\left(CM+HM\right)^2-\left(BM-HM\right)^2\)
\(=CM^2+2CM.HM+HM^2-BM^2+2BM.HM-HM^2\)
\(=2HM\left(CM+BM\right)=2HM.BC\left(đpcm\right)\)
ab + ac + b2 + c2 + 2bc
= a(b + c) + b2 + 2bc + c2
= a(b + c) + (b + c)2
= (b + c)(a + b + c)